2016
DOI: 10.18632/oncotarget.8284
|View full text |Cite
|
Sign up to set email alerts
|

PGE2-EP3 signaling pathway contributes to protective effects of misoprostol on cerebral injury in APP/PS1 mice

Abstract: Epidemiological studies indicate chronic use of non-steroidal anti-inflammatory drugs (NSAIDs), which inhibit the enzymatic activity of the inflammatory cyclooxygenases (COX), reduces the risk of developing Alzheimer's disease (AD) in normal aging populations. Considering multiple adverse side effects of NSAIDs, findings suggest that COX downstream prostaglandin signaling function in the pre-clinical development of AD. Our previous study found that misoprostol, a synthetic prostaglandin E2 (PGE2) receptor agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Therefore, oxidative injury represents a potential target of AD therapy. In the present study, 8-monthold APP/PS1 mice showed significant oxidative damage, as evidenced by the increased MDA content and inhibition of the antioxidant enzymes CAT and SOD, consistent with the findings reported by Tian et al and Wang et al [33,34]. However, the silibinin treatment significantly attenuated oxidative damage in APP/PS1 mice.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, oxidative injury represents a potential target of AD therapy. In the present study, 8-monthold APP/PS1 mice showed significant oxidative damage, as evidenced by the increased MDA content and inhibition of the antioxidant enzymes CAT and SOD, consistent with the findings reported by Tian et al and Wang et al [33,34]. However, the silibinin treatment significantly attenuated oxidative damage in APP/PS1 mice.…”
Section: Discussionsupporting
confidence: 93%
“…Morris water maze was used to evaluate spatial learning and memory function of rat in each group (Kemppainen et al, 2014; Tian et al, 2016). Rats were given four trials per day for four consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…At week 18, a Morris water maze test was performed in all rats as previously described. 28 The temperature of the water was maintained between 20 and 25 °C. The test program included two stages, with the first stage being the navigation training, which lasted for 4 days.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…At week 18, a Morris water maze test was performed in all rats as previously described . The temperature of the water was maintained between 20 and 25 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%